Development and validation of a Multidimensional Motivations to Study Abroad Scale (MMSAS) among European Credit Mobility Students. (March 2018) - Aresi, Giovanni; Alfieri, Sara; Lanz, Margherita; Marta, Elena; Moore, Simon
Abstract: The aim was to establish and validate the Multidimensional Motivations to Study Abroad Scale (MMSAS) to measure university Credit Mobility Students' (CMSs) reasons (e.g., academic, cross-cultural, personal growth) for studying abroad. The instrument was administered to a multi-language sample of 1333 European CMSs. The final measure included 27 items. Results supported nine factors for the English (both for native English speakers and the version for non-native English speakers), French, German, Italian, and Spanish versions; invariance across languages was demonstrated and evidence for construct validity is provided. Further research should explore the relevance of this measure to other populations (e.g., other languages, degree mobility students) and determine the relationship with students' experiences and behaviours abroad.